HUBUNGAN ANTARA KOMPENSASI FINANSIAL DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYWAN PADA PT ARTEJE KAYU ARO - Sudirman, Sudirman; Baviga, Rio; Hendra, Hendra (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the effect of financial compensation and work motivation on employee loyalty at PT Arteje Kayu Aro, a company engaged in the production of bottled drinking water in Kerinci Regency, Jambi Province. The background of this study is based on the phenomenon of increasing turnover and decreasing employee loyalty, which is suspected to be influenced by dissatisfaction with the compensation system and low work motivation. This study uses an explanatory quantitative approach with a population of all 45 permanent employees of PT Arteje Kayu Aro. Due to the relatively small population size, the sampling method used is census sampling. Primary data was collected through a five-point Likert scale questionnaire, while secondary data was obtained from company documents and supporting literature. Data analysis was performed using validity, reliability, and classical assumption tests, as well as multiple linear regression analysis with the help of SPSS version 26 to test the partial and simultaneous effects between variables. Correlation analysis showed that financial compensation has a positive and significant relationship with employee loyalty, while work motivation also shows a positive and significant relationship. Simultaneously, both variables have a very strong relationship with employee loyalty, which means that the better the financial compensation and the higher the work motivation, the higher the loyalty shown by employees. The results of this study emphasize the importance of companies in improving their compensation systems and increasing factors that motivate employees in order to strengthen loyalty and improve organizational sustainability